AN ANALYSIS OF ENGLISH EDUCATION STUDENTS' INTEREST IN THE TEACHING PROFESSION - Akbar Eisenring, Moh. Abraham; Sadilia, Sukmawati; Nirwana, Nirwana; B. Watun, Anasthasia (Tadulako University, 2025)
The teaching profession in Indonesia is highly esteemed, yet it faces challenges in attracting widespread interest. Students of the Faculty of Teacher Training and Education (FKIP) at Tadulako University, particularly those in the English Education program, are projected to become future educators. However, not all of them share an equal level of interest in the profession. Several factors, such as external influences and perceptions regarding the prestige of the profession, significantly affect their career choices. This study aims to analyze the interest of English Education students in the teaching profession after completing the Educational Profession course. Understanding their level of interest in detail and exploring the role of teachers in the modern era is crucial. This study employed a descriptive quantitative approach using a cross-sectional survey design. The research subjects were seventh-semester students of the English Education program who had completed the Educational Profession course during the 2023/2024 academic year, totaling 161 individuals. At least 50% of this population was randomly selected to participate as the study sample. The research instrument was a closed-ended questionnaire using a 4-point Likert scale: strongly disagree, disagree, agree, and strongly agree—to measure students' interest in the teaching profession. The responses were analyzed using descriptive statistics to determine the percentage for each item and describe the general interest of English Education students in becoming teachers.